The carbon and oxygen K-edge NEXAFS spectra of CO+. Issue 28 (9th July 2020) - Couto, Rafael C.; Kjellsson, Ludvig; Ågren, Hans; Carravetta, Vincenzo; Sorensen, Stacey L.; Kubin, Markus; Bülow, Christine; Timm, Martin; Zamudio-Bayer, Vicente; von Issendorff, Bernd; Lau, J. Tobias; Söderström, Johan; et al.
Abstract : We present and analyze high resolution near edge X-ray absorption fine structure (NEXAFS) spectra of CO + at the carbon and oxygen K-edges. Abstract : We present and analyze high resolution near edge X-ray absorption fine structure (NEXAFS) spectra of CO + at the carbon and oxygen K-edges. The spectra show a wealth of features that appear very differently at the two K-edges. The analysis of these features can be divided into three parts; (i) repopulation transition to the open shell orbital – here the C(1s) or O(1s) to 5σ transition, where the normal core hole state is reached from a different initial state and different interaction than in X-ray photoelectron spectroscopy; (ii) spin coupled split valence bands corresponding to C(1s) or O(1s) to π* transitions; (iii) remainder weak and long progressions towards the double ionization potentials containing a manifold of peaks. These parts, none of which has correspondence in NEXAFS spectra of neutral molecules, are dictated by the localization of the singly occupied 5σ orbital, adding a dimension of chemistry to the ionic NEXAFS technique.